Levels of ingested debris vary across species in Canadian Arctic seabirds. Issue 1 (15th March 2017) - Poon, Florence E.; Provencher, Jennifer F.; Mallory, Mark L.; Braune, Birgit M.; Smith, Paul A.
Abstract: Plastic debris has become a major pollutant in the world's oceans and is found in many seabird species from low to high latitudes. Here we compare levels of plastic ingestion from two surface feeders, northern fulmars ( Fulmarus glacialis ) and black-legged kittiwakes ( Rissa tridactyla ), and two pursuit diving species, thick-billed murres ( Uria lomvia ) and black guillemots ( Cepphus grylle ) in the Canadian high Arctic. This is the first report quantifying plastic ingestion in kittiwakes in this region, and as predicted, kittiwakes and fulmars had higher frequency of plastic ingestion than guillemots and murres. Despite this, amounts of plastic ingested by birds remain lower than regions farther south. Highlights: Debris ingestion differed across seabirds with varying feeding strategies. Surface feeders exhibited higher frequency of plastic ingestion than diving birds. Fulmars and murres accumulated similar levels of debris in 2008 and 2013. Regular, standardized monitoring of plastic ingestion in Arctic Canada is required.